Outlining an Intelligent Tutoring System for a University Cooperation Information System - Laaziri, M.; Khoulji, S.; Benmoussa, K.; Larbi, K. M. (Engineering, Technology & Applied Science Research, 2018)
International opening of universities and research institutions is essential in the development of their research and innovation activities. Abdelmalek Essaadi University (AEU) attaches crucial importance to partnership and international cooperation, and actively participates in national and international cooperation and exchange programs. In order to manage the monitoring and evaluation of its cooperation activities as it evolves, the University has set up a system of information on the governance of university cooperation for proper management and managing better partnerships. When setting up a new information system, end-user training in this new management tool is a very important part of this process. For this reason, the University has adopted the idea of developing an intelligent tutoring system. This system will be based on the Moodle platform and will be fully automated and adaptable to the needs of each learner. This article presents the basic design of the intelligent tutoring system incorporated in the management information system of university cooperation SIMACoop of our university and shows the feasibility of the intelligent tutoring system around an information system.